A neuromuscular training program enhances dynamic neuromuscular control and physical performance in court-sport athletes - Gee, T. I.; Morrow, R. A.; Stone, M. R.; Bishop, D. C. (Translational Sports Medicine, 2020)
This study aimed to investigate the effects of an 8-week neuromuscular training protocol on dynamic neuromuscular control and physical performance. Twenty female court-sport athletes were randomly allocated to two groups, a control (n = 10) and an intervention group (n = 10). All participants performed pre-testing inclusive of a 20-m sprint, countermovement jump (CMJ), Illinois agility test, and the qualitative analysis of a single-leg squat (QASLS), which is an assessment of dynamic neuromuscular control. Subsequently the intervention group engaged in a modified version of the FIFA 11+ neuromuscular training program twice weekly for 8 weeks. At post-testing, there were between-group differences in CMJ (intervention; +3.96-cm vs control; -1.36-cm, P = .003) and QASLS for both legs (P < .001) (right leg, intervention; pre: 3.75, post: 1.91, and control; pre: 4.11, post: 4.08) (left leg, intervention; pre: 3.72, post: 0.98, and control; pre: 4.05, post: 4.23). There was a within-group improvement in 20-m sprint for the intervention group only post-training (pre: 3.69-seconds; post: 3.60-seconds, P = .043), while no differences occurred in Illinois agility test for either group. A modified FIFA 11+ protocol can be considered an effective neuromuscular training program for enhancing dynamic neuromuscular control and sport-specific physical performance in female court-sport athletes.